Evaluation of damage mechanisms in tight gas reservoirs: Integration of laboratory experiments and field data with numerical simulation - Bahrami, N. (Society of Petroleum Engineers, 2015)
Tight gas reservoirs represent a significant portion of natural gas reservoirs worldwide. Production at economical rates from tight gas reservoirs in general is very challenging not only due to the very low intrinsic permeability but also as a consequence of several different forms of formation damage that can occur during drilling, completion, stimulation, and production operations. Tight gas reservoirs generally do not produce gas at commercial rates, unless the well is completed using advanced technologies and efficiently stimulated. Well productivity in tight gas reservoirs is largely controlled by formation damage mechanisms such as liquid invasion damage into the low permeability rock matrix that reduces the near wellbore permeability as a result of temporary or permanent trapping of liquid inside the porous media. In many cases of tight gas reservoirs, the key factors that control well productivity and formation damage mechanisms are not well understood, since it is challenging to characterise them in tight formations. This paper presents evaluation of damage mechanisms and characterization of dynamic parameters in tight gas reservoirs and proposes the methods that can provide improved well productivity by minimizing damage to the tight formation. Numerical reservoir simulation is integrated with tight gas field data analysis and core flooding experiments to better understand the effect of different damage mechanisms on well productivity in order to propose the possible remedial strategies that can help achieve viable gas production rates from tight gas reservoirs. Â© Copyright 2015, Society of Petroleum Engineers.